The Conformity of The Legal Concept of a Sole Shareholder Limited Liability Company With That of A Limited Liability Company as a Legal Entity - Letizia Dessy Andreassari; Salmaa Puspita Sari (University of Merdeka Malang, 2025)
This research is motivated by the current legal phenomenon with the Omnibus Law on Job Creation, which allows the establishment of Limited Liability Companies with only one person, known as a sole proprietorship (as referred to in this law). This company is formed by electronically filling out the required forms through the Ministry of Law and Human Rights (Article 13 of Minister of Law and Human Rights Regulation Number 21 of 2021 concerning the Requirements and Procedures for the Registration of Establishment, Changes, and Dissolution of Limited Liability Companies). In this context, the individual acts as the founder, shareholder, and concurrently as the director of the sole proprietorship. One of the main differences in the form of a company lies in the aspect of liability. In the legal context, both the Limited Liability Company as a sole proprietorship and the Limited Liability Company as a corporate legal entity are recognized as legal entities with rights and legal obligations. Therefore, the conformity of the legal concept of the Limited Liability Company as a sole proprietorship with the Limited Liability Company as a corporate legal entity depends on compliance with the requirements and legal provisions applicable to each form of the Limited Liability Company, taking into account the business and financial needs of the company owner. The two issues addressed in this research are the nature of the Limited Liability Company as a Legal Entity and the conformity of the legal concept of the Limited Liability Company as a sole proprietorship with the Limited Liability Company as a Corporate Legal Entity. In line with the focus and issues raised, this research employs a normative method that considers law as a normative system. The research relies on documents, primarily regulations in Civil Law, Commercial Law, and Law Number 40 of 2007 concerning Limited Liability Companies to explain and address the conformity of the legal concept of the Limited Liability Company as a sole proprietorship with the Limited Liability Company as a corporate legal entity.